The Concept of Renovation (Salam International Academic Journal, 2011)
This paper dealt with "the concept of renovation" at the beginning this research paper stressed on the linguistic meaning and definition of the word "renewal", for this purpose he recalled all meanings of the word in dictionaries.     Then the researcher mentioned the meanings of the term in the Qur'an and Sunnah, and based on these meanings, he clarified the conventional meaning of this terminology.       For further clarification, the paper reports some characteristics of the term "renovation" in Islam, and stressed on that these characteristics must be taken into account in the clarification of the term "renewal".      Then the paper quoted a group of former and contemporary Muslim scholars about the definition of "renovation", and in light of those quotations, the paper specified the areas of "renewal" in Islam, supporting his viewpoint the paper mentioned the decisions of some academic conferences as well as statements of some contemporary Muslim scholars.
Keywords: Renovation; Reformer; Western Colonialism; Intellectual War; Religiosity